El comentario de textos a través de los silencios. Cervantes y su tiempo: Entre el deseo de decir y la conveniencia de callar - Díez Coderque, Belén (Didáctica. Lengua y Literatura, 2006)
Starting from a study of silences in El Quijote, a text commentary is commentary is proposed in this article, based on silences research. This way to approach the critical and curious reading may be producing stimulating and important effects on the students. In fact, studying one particular element of this artistic job we may discover the mechanism work of his production, his narratives and pargmatics strategies.